Megarectum: systematic histopathological evaluation of 35 patients and new common pathways in chronic rectal dilatation. Issue 10 (25th May 2021) - Martin, Joanne E; English, William; Kendall, John V; Sheshappanavar, Vinayata; Peroos, Sara; West, Milly; Cleeve, Stewart; Knowles, Charles
Abstract : Aims: Megarectum is well described in the surgical literature but few contemporary pathological studies have been undertaken. There is uncertainty whether 'idiopathic' megarectum is a primary neuromuscular disorder or whether chronic dilatation leads to previously reported and unreported pathological changes. We sought to answer this question. Methods: Systematic histopathological evaluation (in accord with international guidance) of 35 consecutive patients undergoing rectal excision surgery for megarectum (primary: n=24) or megarectum following surgical correction of anorectal malformation (secondary: n=11) in a UK university hospital with adult/paediatric surgical and gastrointestinal neuropathology expertise. Results: We confirmed some previously reported observations, notably hypertrophy of the muscularis propria (27 of 35, 77.1% of patients) and extensive fibrosis (30 of 35, 85.7% of patients). We also observed unique and previously unreported features including elastosis (19 of 33, 57.6%) and the presence of polyglucosan bodies (15 of 32, 46.9% of patients). In contrast to previous literature, few patients had any strong evidence of specific forms of visceral neuropathy (5 of 35, including 3 plexus duplications) or myopathy (6 of 35, including 3 muscle duplications). All major pathological findings were common to both primary and secondary forms of the disease, implying that these may be a response to chronic rectal distension rather than of primary aetiology. Conclusions: In the largest case series reported to date, we challenge the current perception of idiopathic megarectum as a primary neuromuscular disease and propose a cellular pathway model for the features present. The severe morphological changes account for some of the irreversibility of the condition and reinforce the need to prevent ongoing rectal distension when first identified.